The Influence of Institutional Logics on Corporate Responsibility Toward Employees. (September 2014) - Westermann-Behaylo, Michelle; Berman, Shawn L.; Van Buren, Harry J.
Focusing on corporate responsibility (CR) toward employees, this article discusses how multilayered institutional logics affect the relationship between the firm and its employee stakeholders. It considers what constitutes CR toward employees and explores the institutional logics that can shape whether employers treat their employees as merely means to a strategic end or as ends in themselves. Specifically, the article examines market-, state-, professional-, and firm-based institutional logics that influence how employers treat their employees. The conclusion suggests that external institutional logics both enable and constrain firms to adopt a more instrumental relationship with their employees. However, some forms of organizational identity may generate firm-based institutional logics that enable firms to resist these pressures. Suggestions for future research focusing on the institutional and organizational drivers behind understanding CR toward employees are offered.